Team-Based Care for Improving Hypertension Management: A Pragmatic Randomized Controlled Trial - Santschi, Valérie; Wuerzner, Gregoire; Pais, Bruno; Chiolero, Arnaud; Schaller, Philippe; Cloutier, Lyne; Paradis, Gilles; Burnier, Michel (Frontiers in Cardiovascular Medicine, 2021)
Objective: We evaluated the effect on long term blood pressure (BP) of an interprofessional team-based care (TBC) intervention, involving nurses, pharmacists, and physicians, compared to usual care. Methods: We conducted a pragmatic randomized controlled study in ambulatory clinics and community pharmacies in Switzerland (ClinicalTrials.gov: NCT02511093). Uncontrolled treated hypertensive patients were randomized to TBC or usual care (UC). In the TBC group, nurses and pharmacists met patients every 6 weeks to measure BP, assess lifestyle, support medication adherence, and provide health education for 6 months. After each visit, they wrote a report to the physician who could adjust antihypertensive therapy. The outcome was the intention-to-treat difference in mean daytime ambulatory BP measurement (ABPM) and control (<135/85 mmHg) at 6 and 12 months. Results: Eighty-nine patients (60 men/29 women; mean (SD) age: 61(12) year) were randomized to TBC (n=43) or UC (n=46). At baseline, mean (SD) BP was 144(10)/90(8) mmHg and 147(12)/87(11) mmHg in the TBC and UC groups. At 6 months, the between-groups difference in daytime systolic ABPM was -3 mmHg [95% confidence interval (CI): -10 to +4; p=0.45]; at 12 months, this difference was -7 mmHg [95% CI: -13 to -2; p=0.01]. At 6 months, the between-groups difference in daytime diastolic ABPM was +2 mmHg [95% CI: -1 to +6; p=0.20]; at 12 months, this difference was -2 mmHg [95% CI: -5 to +2; 0.42]. Upon adjustment for baseline covariates including baseline BP, the between-groups differences at 6 and 12 months were maintained. At 6 months, there was no difference in BP control. At 12 months, the TBC group tended to have a better control in systolic BP (p=0.07) but not in diastolic BP (p=0.33). Conclusion: While there was not significant effect on BP at 6 months of follow-up, the TBC intervention can help decrease long-term systolic BP among uncontrolled hypertensive patients.